Peningkatan Prestasi Belajar Siswa Melalui Model Pembelajaran Students Team Achievement Division (STAD) di Kelas IX SMP - Semah Semah (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The purpose of writing this class action research is to find out whether the Student Team Achievement Division (STAD) learning model can improve student learning activities and achievements. The data collection methods are observation and learning achievement tests. The data analysis method is descriptive both for qualitative data and for quantitative data. The results obtained from this study are that the Student Team Achievement Division (STAD) can improve student learning activities and achievements. This is evident from the results obtained in Cycle I increased by 60% and from Cycle I to Cycle II rose 92%. The conclusion obtained from this study is that the Student Team Achievement Division (STAD) learning model can improve learning activities and achievements.